The effects of eccentric training on undulatory underwater swimming performance and kinematics in competitive swimmers - Ruiz-Navarro, J. J.; López-Belmonte, Ó.; Cuenca-Fernández, F.; Gay, A.; Arellano, R. (Journal of Human Kinetics, 2024)
This study aimed to evaluate the effects of a five-week training program on undulatory underwater swimming (UUS) in swimmers and to compare the specific effects prompted by two different training protocols on UUS performance and kinematics. Swimmers (n = 14) were divided into in-water only (WO) (18.61 ± 2.62 years, FINA points: 507 ± 60) and water + dry-land training groups (with conical pulleys) (WD) (18.38 ± 2.67 years, FINA points: 508 ± 83). Three countermovement jumps (CMJ) and three maximal UUS trials were performed before and after a five-week training period. The training program comprised 14 × 30-min sessions. The WO group repeated the same 15-min block twice, while the WD group performed one block of 15 min in the water and the other block on land performing lower limb exercises with conical pulleys. Seven body landmarks were auto-digitalized during UUS by a pre-trained neural network and 21 kinematic variables were calculated. The level of statistical significance was set at p < 0.05. Significant time × group interaction in favour of the WD group was observed for mean vertical toe velocity (p = 0.035, = 0.32). The WD group experienced enhancements in mean and maximum underwater velocity, kick frequency, maximum shoulder angular velocity, as well as mean and maximum vertical toe velocity (p < 0.05). The WO group exhibited an enhancement in CMJ height (p < 0.05). In conclusion, UUS performance was improved in adolescent swimmers after five weeks of specific training, only when combining water and conical pulley exercises. Coaches should include dry-land specific lower limb exercises in addition to in-water training to improve UUS performance.